PENGEMBANGAN MODUL IDENTIFIKASI INSEKTA DI BKPH KEDUNGGALAR KECAMATAN PITU NGAWI PADA MATA KULIAH TAKSONOMI HEWAN INVERTEBRATA - Kusumaningrum, Nur Aini (Jurnal Florea, 2015)
Invertebrate taxonomy module courses are limited and textual. Invertebrate taxonomy module that isnot based on contextual research. Ngawi Pitu forest can be used as a location for research, because ofthe diversity of existing invertebrates. The research aims to develop insect identification modules onsubjects Taxonomy invertebrate insightful context. Module development using the 4D model (Define,Design, Development, Dissemination). The products produced in the form of modules with productvalidation to experts and tested on students. The results obtained expert ideals 79 % in both categories.Results of tests on subjects obtained ideals 72% with the good category. The trial results states : 1 )modules developed well and fit for use with the improvement of writing, 2 ) students easily recognizeexamples of insects as obtained from the forest and the surrounding environment. Suggestiondevelopment need to be large-scale trials to determine the effectiveness of the module as well as needto be developed on a wider material .Keywords: identification, insects, modules